Infants' predictive minds: The role of motor experience - Schwarzer, Gudrun; Jovanovic, Bianca; Justus Liebig University Giessen (My University, 2024)
The ability to predict upcoming events is essential in infancy because it enables babies to process information optimally and have successful goal-directed interactions with their environment. In this article, we examine how infants generate predictions in perception, cognition, and action, and address whether and how their predictions are motivated and affected by their motor development. Our synthesis of research demonstrates that infants form predictions in the perception, cognition, and action domains based on perceived statistical information, pre-existing and newly generated knowledge, and internal motor models. Our analysis reveals that infants' increasing fine and gross motor experiences have a moderating impact on the elaboration of the different bases for predictions. Based on this, we conclude that new motor experiences enable infants to constantly improve the bases from which they generate and update their predictions.
Keywords: ddc:150